2019
DOI: 10.5213/inj.1938112.056
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ultrasound-Guided Transgluteal and Finger-Guided Transvaginal Pudendal Nerve Block Techniques: Which One is More Effective?

Abstract: Pudendal neuralgia (PN) is a painful and disabling condition, which reduces the quality of life as well. Pudendal nerve infiltrations are essential for the diagnosis and the management of PN. The purpose of this study was to compare the effectiveness of finger-guided transvaginal pudendal nerve infiltration (TV-PNI) technique and the ultrasound-guided transgluteal pudendal nerve infiltration (TG-PNI) technique. Methods: Forty patients who underwent PNI for the diagnosis of PN were evaluated. Thirty-five of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
1
15
0
1
Order By: Relevance
“…However, in traditional obstetric PDB placed by midwives and obstetricians, using the finger to identify the pelvic landmarks is a time-tested and feasible way of ensuring optimal placement of the local anesthetic around the pudendal nerve. Also, a recent study comparing digitally guided transvaginal PDB with ultrasound guided trans-gluteal PDP for pudendal neuralgia showed these methods to be equally as effective [14]. Our digitally guided trans-gluteal technique was effective for pain relief in the two women needing rescue PDB.…”
Section: Discussionmentioning
confidence: 61%
“…However, in traditional obstetric PDB placed by midwives and obstetricians, using the finger to identify the pelvic landmarks is a time-tested and feasible way of ensuring optimal placement of the local anesthetic around the pudendal nerve. Also, a recent study comparing digitally guided transvaginal PDB with ultrasound guided trans-gluteal PDP for pudendal neuralgia showed these methods to be equally as effective [14]. Our digitally guided trans-gluteal technique was effective for pain relief in the two women needing rescue PDB.…”
Section: Discussionmentioning
confidence: 61%
“…When the entire pelvic floor is involved, administering a pudendal nerve block can provide similar relief while minimizing the number of injections required. This can be done in the office setting, using exactly the same procedure as one would use for women in labor 48,49 . There is no research exploring the use of pudendal blocks in MPPS, although its use in treating pudendal neuralgia is documented 48 .…”
Section: Treatment For Myofascial Painmentioning
confidence: 99%
“…This can be done in the office setting, using exactly the same procedure as one would use for women in labor 48,49 . There is no research exploring the use of pudendal blocks in MPPS, although its use in treating pudendal neuralgia is documented 48 . Contraindications to anesthetic injections include anticoagulation or bleeding disorders, local infection, suspected abdominal hernia, and allergy to anesthetic.…”
Section: Treatment For Myofascial Painmentioning
confidence: 99%
“…A randomized controlled trial by Bellingham et al showed that injections with a mixture of a long-acting local anesthetic and corticosteroids performed either by fluoroscopic or US guidance are equally effective (78) . Due to the vicinity of the sciatic nerve, a temporary adverse effect of numbness or foot drop may develop following the injection (73) .…”
Section: Pudendal Neuralgiamentioning
confidence: 99%
“…According to the Nantes criteria published by Labat et al ., at least five clinical presentations must be present in order to diagnose pudendal neuralgia: (1) pain in the pudendal nerve innervation area, (2) predominantly while sitting, (3) not present during the night, (4) without any objective sensory impairment, and (5) relieved after the pudendal nerve block ( 72 ) . US-guided injections represent the best diagnostic and treatment options ( 5 , 73 ) . MRI is considered in diagnostic dilemmas in order to exclude structural abnormalities in the course of the pudendal nerve ( 68 , 74 ) .…”
Section: Pudendal Neuralgiamentioning
confidence: 99%